2005
DOI: 10.1039/b502641e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of the perovskite-related cuprate phases YSr2Cu2MO7+y(M = Co, Fe) for potential use as solid oxide fuel cell cathode materials

Abstract: In this paper we report the synthesis and characterisation of the perovskite cuprate phases YSr 2 Cu 2 MO 7+y (M=Co, Fe) to examine their potential for use as cathode materials in Solid Oxide Fuel Cells (SOFC). Both samples showed conductivities of ≈10 Scm -1 at 900°C and were also shown to be stable at this temperature in N 2 . For YSr 2 Cu 2 FeO 7+x , semiconducting behaviour was observed up to ≈550°C, with a decrease in conductivity at higher temperatures, attributed to oxygen loss reducing the charge carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…For example, oxygen vacancies have been shown to directly affect kinetics of both OER and ORR in these materials, and oxygen hyperstoichiometry influences catalytic activity by providing access to high valent oxidation states of transition metals within the lattice . The high ionic conductivity with respect to O 2− anions has also made RPOs a central focus in solid oxide fuel cells, resulting in the synthesis and structural characterization of a large selection of ternary and quaternary compositions . The comprehensive electrochemical behavior of RPO materials is not typically explored in detail.…”
Section: Introductionmentioning
confidence: 99%
“…For example, oxygen vacancies have been shown to directly affect kinetics of both OER and ORR in these materials, and oxygen hyperstoichiometry influences catalytic activity by providing access to high valent oxidation states of transition metals within the lattice . The high ionic conductivity with respect to O 2− anions has also made RPOs a central focus in solid oxide fuel cells, resulting in the synthesis and structural characterization of a large selection of ternary and quaternary compositions . The comprehensive electrochemical behavior of RPO materials is not typically explored in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The orthorhombic 3a p structure of YSr 2 Cu 2 CoO 7 (illustrated in Fig. 1) was first reported by Huang et al [29], and a later study at high temperature showed that it undergoes a transformation to a tetragonal structure above 800 C [30]. This compound is a layered perovskite, with Y, Sr, Co and Cu layers ordered along the stacking axis.…”
Section: Introductionmentioning
confidence: 87%
“…The electronic properties of YSr 2 Cu 2 MO 7þd (M ¼ Fe, Co) were studied by Sansom et al [30,31], who reported a p-type semiconductor with a total conductivity of 15 S cm À1 at 800 C, whilst thermogravimetric analysis showed that no oxygen loss occurred in the temperature range 25e900 C under air and nitrogen atmospheres. The material was found to be reactive towards the common electrolytes La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 2.85 , YSZ, GDC and apatite at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The change of oxidation states of the mixed valence cations influences the conductivity values due to the concentration of electron carriers (holes, h • ). The work carried out by Sansom et al [47] on cuprates with the 1:2:3 structure, YSr 2 Cu 2 CoO 7 and YSr 2 Cu 2 FeO 7 , also reports a hysteresis in conductivity values between measurements performed in reducing and oxidizing conditions, which is assigned to a poor oxide ion transport, poor oxygen surface exchange kinetics, or significant structural changes on varying oxygen partial pressure. For YBCO, different resistivity values during cooling and heating were measured even with ramps of 0.1°C min − 1 .…”
Section: Conductivity Measurementsmentioning
confidence: 98%